Environmental relevance in Peruvian medicine in relation to the story «Los polvos de la condesa» - Calderón Carrillo, Adrian Marcos (2020)
In this article I will analyse the story «Los polvos de la condesa», written by Ricardo Palma. I will make an approximation of the story with a central nucleus focused on the environment and nature; additionally, I will mention how these are used by galenic practitioners in viceregal Lima to treat different pathologies of the time.